Does Greater Autonomy among Women Provide the Key to Better Child Nutrition? - Wiji Arulampalam; Anjor Bhaskar; Nisha Srivastava (Institute for the Study of Labor (IZA), 2016)
We examine the link between a mother's autonomy – the freedom and ability to think, express, act and make decisions independently – and the nutritional status of her children. We design a novel statistical framework that accounts for cultural and traditional environment, to create a measure of maternal autonomy, a concept that has rarely been examined previously as a factor in children's nutritional outcomes. Using data from the Third Round of the National Family Health Survey for India, supplemented with our qualitative survey, and accounting for "son preference" by limiting analysis to first-born children under 18 months of age, we document that maternal autonomy has a positive impact on the long-term nutritional status of rural children. We find that one standard deviation increase in maternal autonomy score (i) is associated with a 10 percent reduction (representing 300,000 children) in the prevalence of stunting, and (ii) compensates for half of the estimated average decline in Height-for-Age Z-scores Indian children experience in the second six months of life. The findings underscore the importance of women's empowerment in improving children's nutrition during the critical first two years of life, a recognized "window of opportunity" for lifelong health and economic benefits.
Keywords: C38; I14; I18; 330; child nutrition; maternal autonomy; latent factor models; empirical Bayes; India; National Family Health Survey